Global Prevalence of Antibiotic-Resistant Burkholderia pseudomallei in Melioidosis Patients: A Systematic Review and Meta-Analysis - Jongkonnee Thanasai; Sa-Ngob Laklaeng; Supphachoke Khemla; Khonesavanh Ratanavong; Moragot Chatatikun; Jitbanjong Tangpong; Wiyada Kwanhian Klangbud (Antibiotics)
Background: Burkholderia pseudomallei, the causative agent of melioidosis, is intrinsically resistant to multiple antibiotics, posing substantial challenges for treatment. Reports of acquired resistance are increasing, underscoring the need for global surveillance. Objective: This systematic review and meta-analysis aimed to determine the global prevalence of antibiotic-resistant B. pseudomallei isolated from human clinical cases, with a focus on regional differences and variations in antimicrobial susceptibility testing methods. Methods: We systematically searched PubMed, Scopus, and Embase for studies reporting resistance in clinical B. pseudomallei isolates, following PRISMA guidelines. Pooled resistance rates to 11 antibiotics were calculated using a random-effect model. Subgroup analyses were performed based on geographical region and testing methodology (MIC vs. disk diffusion). Results: Twelve studies comprising 10,391 isolates were included. Resistance rates varied across antibiotics, with the highest pooled resistance observed for tigecycline (46.3%) and ciprofloxacin (38.3%). Ceftazidime (CAZ) and trimethoprim–sulfamethoxazole (SXT), commonly used first-line agents, showed resistance rates of 5.3% and 4.2%, respectively. Subgroup analyses of CAZ and SXT revealed significantly higher resistance in studies from Asia compared to Australia and America (p value < 0.0001). Disk diffusion methods tended to overestimate resistance compared to MIC-based approaches, which revealed non-significant differences for CAZ (p value = 0.5343) but significant differences for SXT (p value < 0.0001). Conclusions: Antibiotic resistance in B. pseudomallei exhibits regional variation and is influenced by the susceptibility testing method used. Surveillance programs and standardized antimicrobial susceptibility testing protocols are essential to guide effective treatment strategies and ensure accurate resistance reporting.